2008
DOI: 10.1021/jp711219e
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Study of Water-Soluble CdS Nanoparticles Produced by Femtosecond Laser Ablation at High Laser Fluence

Abstract: Water-soluble CdS nanoparticles (NPs) with excellent colloidal stability were produced by femtosecond laser ablation at high laser fluence. The transmission electron microscope image of the obtained NPs exhibited a presence of two populations, characterized by low and high size dispersions, with different mean particle sizes. A comprehensive optical spectroscopy study of the NPs was carried out, and the results indicated a close correlation between the distribution properties and the luminescence characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…CdS nanoparticles with different morphologies, such as spherical and hollow spherical nanoparticles, were synthesized by using PLAL and showedablueshift to highere nergies in the optical bandgap [14] due to the size quantization effect. [11,12,13,29] The redshift (1.8 to 2.1 eV) observed in the CdS colloidss ynthesized by ablationa tl = 1064 nm may be due the formation of agglomerated CdS nanoparticles or the presence of otherp hases.C dS nanoparticles were synthesized by ablation in ag as medium at laser wavelengths of l = 266 and 355 nm, and ar edshift was observed after ablation at l = 355 nm due to the formationo fl arger nanocrystals. Also, an opticalb andgap of 2.33 eV was reported for CdS in aT iO 2 / ZnO/CdS composite synthesized by using PLAL, which represents ar edshift due to the presence of other nanomaterials.…”
Section: Uv/vis Absorption Spectramentioning
confidence: 99%
See 3 more Smart Citations
“…CdS nanoparticles with different morphologies, such as spherical and hollow spherical nanoparticles, were synthesized by using PLAL and showedablueshift to highere nergies in the optical bandgap [14] due to the size quantization effect. [11,12,13,29] The redshift (1.8 to 2.1 eV) observed in the CdS colloidss ynthesized by ablationa tl = 1064 nm may be due the formation of agglomerated CdS nanoparticles or the presence of otherp hases.C dS nanoparticles were synthesized by ablation in ag as medium at laser wavelengths of l = 266 and 355 nm, and ar edshift was observed after ablation at l = 355 nm due to the formationo fl arger nanocrystals. Also, an opticalb andgap of 2.33 eV was reported for CdS in aT iO 2 / ZnO/CdS composite synthesized by using PLAL, which represents ar edshift due to the presence of other nanomaterials.…”
Section: Uv/vis Absorption Spectramentioning
confidence: 99%
“…All the emission spectra present broad peaks in the green region.I th as been reported that green emission peaks around the bulk bandgap energy is assigned as the recombination of free electrons and holes, and also that low-intensity emission peaks indicate that the CdS nanoparticles are not efficientlye xcited, and the broad emission peak implies that al arge number of particles of different sizes are excited. [13] The size variation andm orphological differences in CdS nanoparticles caused by the ablationwavelength, energy,a nd liquid medium resultedi nd ifferent opticale missions. [31] Also, CdS nanoparticles synthesized by using chemical methods displayed al ess intense broad green peak at 2.3 eV and am ore intense peak at 2.5 eV.…”
Section: Room-temperaturephotoluminescence Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Nanocolloids synthesis was completely free of any ligands and was highly stable. Other materials having applications in solar cells and optoelectronics synthesized by PLALM include ZnS [16], PbS [16], SnS [17], CdS [18], Sb 2 S 3 [19], CdTe [20,21], CdSe [21,22] and ZnTe [21]. Here we report synthesis, morphology and properties of CIGS nanoparticles using pulsed laser ablation of a CIGS alloy target in different liquid media by varying the laser fluence and ablation wavelengths.…”
Section: Introductionmentioning
confidence: 98%